Investigating User Experience to Redesign User Interface Using User-Centered Design Approach - A'ang, Subiyakto; Amimah, Amimah; Evy, Nurmiati; Zulfiandri, Zulfiandri; Eri, Rustamaji; Tri, Haryanto; T.K.A, Rahman (2022)
User interface (UI) and user experience (UX) are two essential issues closely interrelated to the easiness, satisfaction, and acceptance perspectives of users. It is how the information technology (IT) products are used by users, one of the critical success criteria of product development. However, this product usability seems often to be ignored in the development process. This study was performed to evaluate the usability of a sampled application, to design UI/UX of the application, to investigate the usability of the proposed design, and to compare results of the preliminary usability evaluations with results of the post-design investigation, in the context of user-centered design (UCD) approach. Five study stages were implemented following the four research purposes. Specifically,the usability evaluations were done by employing cognitive walkthrough (CW), system usability scale (SUS) questionnaires, user experience questionnaire (UEQ), and interview techniques. Besides the proposed prototype, the improvements in success, satisfaction, and acceptance rates presented by the comparison between pre-design and post-design usability evaluations were two highlighted findings. These may be one of the reference designs for the system performance improvement and may also be one of the methodological references for others who are interested in a similar research area by considering the research limitations.